Digital Platforms: A New Grammar for Territories? - Grumbach, Stéphane (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2017)
Digital platforms are reshaping the geometry of the world. Their wide adoption by the population worldwide for an increasing number of activities, confer them a dominant position, which challenges established powers. Their control over the global flow of data and their algorithmic treatment leads to new asymmetries of power. New systems emerge, that unlike the Westphalian States do not correspond to territories on a map, but to complex networks controlling sectors of activities at a global scale. It is a real challenge and a necessity to reinvent a grammar of territories, to be able to grasp the new objects and their dependencies, and address the related issues of social justice and sustainable interaction with our planet.
Keywords: digital platforms; algorithmic intermediation; information asymmetry; local government; division of labour; sovereignty; Anthropocene